2018
DOI: 10.1039/c8ta00779a
|View full text |Cite
|
Sign up to set email alerts
|

Solar-assisted fast cleanup of heavy oil spills using a photothermal sponge

Abstract: Photothermal material-assisted solar-driven heavy oil removal is promising for highly viscous oil-spill cleanup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(77 citation statements)
references
References 37 publications
(38 reference statements)
1
76
0
Order By: Relevance
“…The volumetric ratio of these two types of channels are almost the same in both the natural wood and HC‐Wood, but the total porosity increases from 57.4% to 73.8% after the pyrolysis (Figure h; Figures S6 and S7, Supporting Information). Moreover, unlike other heat‐assisted porous absorbers with low thermal conductivity (<0.2 W m −1 K −1 ), the thermal conductivity of the HC‐Wood along the channel direction ( L ‐direction) is ≈0.6 W m −1 K −1 (Figure i). The improved thermal conductivity of the HC‐Wood can be accredited to the straight and short pathways for thermal transfer along the L ‐direction of the low tortuosity structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volumetric ratio of these two types of channels are almost the same in both the natural wood and HC‐Wood, but the total porosity increases from 57.4% to 73.8% after the pyrolysis (Figure h; Figures S6 and S7, Supporting Information). Moreover, unlike other heat‐assisted porous absorbers with low thermal conductivity (<0.2 W m −1 K −1 ), the thermal conductivity of the HC‐Wood along the channel direction ( L ‐direction) is ≈0.6 W m −1 K −1 (Figure i). The improved thermal conductivity of the HC‐Wood can be accredited to the straight and short pathways for thermal transfer along the L ‐direction of the low tortuosity structure.…”
Section: Resultsmentioning
confidence: 99%
“…However, these absorbents generally focus on the recovery of low‐viscosity oil, while under similar test conditions with viscous crude oil (Viscosity >1000 mPa s), the absorption rate (AR) of previously reported devices is prone to deteriorate. Novel methods using heat to decrease the viscosity of the oil is a promising way to address this issue, but not easily transferable to real‐world situations where the material and operation costs are considered to be extremely critical in addressing the problem of large‐area off‐shore oil spills. Moreover, the thermal property of the absorber and the fluid dynamics of porous systems for oil spills remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the temperature rises, the viscosity gradually decreases. When the temperature rose above 60 °C, the viscosity dropped below 100 mPa s, which is the viscosity of light oils at room temperature . This viscosity drop of the crude oil greatly improved the kinetics of oil absorption.…”
Section: Resultsmentioning
confidence: 99%
“…These increased conjugated π bonds will result in a red-shift of the absorption light spectrum, which greatly benefits in the solar energy utilization efficiency. [75] For example, Wang and co-workers demonstrated that CNT-coated sponges display 99% sunlight harvesting performance, and their surface equilibrium temperature can reach up to 88 °C, [75] implying a remarkable photothermal conversion efficiency. Due to strong absorption property (up to 98% in visible and near-infrared region) [60] and high thermal conductivity (6000 W m −1 k −1 ), [72] these CNT-based photothermal convertors can not only efficiently generate a lot of thermal energy, but also fast transfer thermal energy into surrounding medium via radiation and conduction method.…”
Section: Carbon Nanotube and Graphenementioning
confidence: 99%
“…Sci. [75] Copyright 2018, Royal Society of Chemistry. Photothermal-assisted crude oil cleanup for water purification.…”
Section: Photothermal-enhanced Photocatalysis For Dye Degradationmentioning
confidence: 99%